Analysis of archaeological charcoals from the Later Stone Age sequence of the Prehistoric site of Bushman Rock Shelter, Limpopo, South Africa: From the field to the laboratory work - (:unkn) unknown (My University, 2021)
This PhD project focuses on the first charcoal study of the Later Stone Age sequence of the Bushman Rock Shelter site, Limpopo, South Africa. The site preserves one of the rare terrestrial archives of the Late Pleistocene-Holocene transition, a critical still poorly understood period in the southern African region. The abundant and well-preserved charcoal remains of the site offer a unique opportunity to document the past woody vegetation in the vicinity of the site as well as fuelwood management strategies by human groups occupying the shelter at this period. After a brief presentation of the site and the issues involved in the project, this article describes the methodological approach adopted for the anthracological study, from the collection of charcoal fragments during the excavation to their analysis in the laboratory. Particular attention is paid to the importance of modern comparison material, its acquisition and use, which are essential steps in the identification and interpretation of archaeological data.
Keywords: African Research